1997
DOI: 10.1037/h0080248
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia and AIDS in married men: Functioning of family members.

Abstract: Aspects of functioning in families of 137 hemophilic men who, in 50% of cases, were also HIV seropositive were examined in terms of psychological and physical functioning and economic pressure. Results indicated that HIV-seropositive status, but not severity of hemophilia, was associated with poorer psychological and physical functioning of the husband, a poorer mother-child relationship, less support from outside the family for both spouses, and greater economic pressure on the family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Parents reported a broad range of competing needs as well. Our study and other studies have indicated that HIV-infected parents may have only limited social support from families and friends [32][33][34][35] ; by comparison, previous studies conducted with physically ill and general samples found that only 2% of the people had no close friends or relatives. 36,37 About 20% of the children lived with neither the respondent nor the other parent.…”
Section: Discussionmentioning
confidence: 75%
“…Parents reported a broad range of competing needs as well. Our study and other studies have indicated that HIV-infected parents may have only limited social support from families and friends [32][33][34][35] ; by comparison, previous studies conducted with physically ill and general samples found that only 2% of the people had no close friends or relatives. 36,37 About 20% of the children lived with neither the respondent nor the other parent.…”
Section: Discussionmentioning
confidence: 75%
“…Seven studies had sample size over 1000 [16, 17, 1923], while four studies had sample size below 100 [2427]. Except for one study only collecting data from caregivers [28], all the other studies collected data from children, among which seven studies recruited caregivers as an additional source of information [12, 24, 2933]. …”
Section: Resultsmentioning
confidence: 99%
“…All identified records (n = 288) were initially screened to exclude citations that did not provide quantitative data for children affected by HIV/AIDS (n =124), or that did not focus on psychological well-being of children (n = 71) (e.g., studies on children’s physical development, nutrition, school enrollment, and caregivers’ health), or that did not include a desired comparison group (n = 45). We also hand-searched the reference sections of the previous literature reviews and other relevant articles [3, 79] and retrieved three additional articles [1012]. The search resulted in 51 eligible articles reporting data from a total of 30 studies.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it appears that adolescents whose mothers are HIV-infected tend to exhibit higher rates of externalizing behaviors, whereas younger children of seropositive parents may evidence higher rates of internalizing problems (Esposito et al, 1999;Forsyth et al, 1996;Forehand et al, 1997;Forehand et al, 1998;Forehand et al, 2002), of externalizing problems (Esposito et al, 1999;Forehand et al, 1998), or of both (Bauman et al, 2002;Forehand et al, 1998;Esposito et al, 1999). It is unclear, however, whether this pattern is due to sampling characteristics (i.e., mothers vs. fathers; child age), methodological differences (i.e., failing to measure multiple domains of child functioning and/or measuring them in different ways and from different sources), or some combination Child Psychosocial Adjustment 5 thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies that have investigated whether parental HIV/AIDS is associated with youth adjustment problems seem to suggest that non-infected children living in families affected by parental HIV/AIDS demonstrate higher rates of maladjustment relative to children living in families not coping with parental illness (Bauman, Camacho, Silver, Hudis, & Draimin, 2002;Esposito et al, 1999;Forehand et al, 1997;Forehand Child Psychosocial Adjustment 4 et al, 1998;Forsyth et al, 1996;Lester, Stein, & Bursch, 2003;Rotheram-Borus & Stein, 1999).…”
Section: Introductionmentioning
confidence: 99%